Mutational analysis of the structure and biogenesis of the photosystem I reaction center in the cyanobacterium Synechocystis sp. PCC 6803. - Smart, L B (1993)
We have utilized the unicellular cyanobacterium Synechocystis sp. PCC 6803 to incorporate site-directed amino acid substitutions into the photosystem I (PSI) reactioncenter protein PsaB. A cysteine residue (position 565 of PsaB) proposed to serve as a ligand to the [4Fe-4S] center Fx was changed to serine, histidine, and aspartate. These three mutants--C565S, C565H, and C565D--all exhibited greatly reduced accumulation of PSI reaction-center proteins and failed to grow autotrophically, indicating that this cysteine most likely does coordinate Fx, which is crucial for PSI biogenesis. Interestingly, the strain C565S accumulated significantly more PSI than the other two cysteine mutants and displayed photoreduction of the [4Fe-4S] terminal electron acceptors FA and FB. Mutations were also introduced into a leucine zipper motif of PsaB, proposed to participate in reaction-center dimerization. The mutants L522V, L536M, and L522V/L536M all exhibited wild-type characteristics and grew autotrophically, whereas the L522P mutation prevented PSI accumulation. These data do not provide support for a major structural role of the leucine zipper in reaction-center dimerization or in assembly of Fx. However, the amino acid substitutions incorporated were conservative and might not have perturbed the leucine zipper.